A Legend of Computational Fluid Dynamics and an Eminent Mathematician: Professor Md. Anwar Hossain - Kamrujjaman, M; Molla, M Mamun; Kabir, MH; Biswas, MHA; Khan, MAH (GANIT: Journal of Bangladesh Mathematical Society, 2022)
Abstract not available GANITJ. Bangladesh Math. Soc.41.2 (2021) 1-4